PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP BIAYA MODAL EKUITAS - jovy, muhammad jovy shidqy; Suranta, Eddy; Midiastuty, Pratana Puspa (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
The aim of this research is to examine and obtain evidence regarding the relationship between audit committee characteristics and the cost of equity capital in the banking sector. The dependent variable in this research is the cost of equity and is calculated using the earning price approach method. The independent variables in this research are the characteristics of the audit committee which consist of size, financial expertise, frequency of meetings, proportion of the audit committee that is female and tenure. Then what was used as a sample in this research were banking companies listed on the Indonesia Stock Exchange during the 2015-2021 period with several sample criteria which were determined at the beginning of the research so that the number of observations used in this research was 98 observations with a total of 18 companies. . The research results prove that the size of the audit committee, the frequency of audit committee meetings and the tenure of the audit committee have a positive influence on the cost of equity capital. The audit committee's financial expertise has no influence on the cost of equity capital. The proportion of the audit committee that is female has a negative influence on the cost of equity capital.